Surface roughness condition of field-aged polymer insulators at different installation area - A. Din; M.A. M. Piah; A. R. Abdullah; N. F. Kasri (Institute of Advanced Engineering and Science, 2019)
This paper presents surface degradation assessment based on surface roughness condition for various field-aged high voltage polymer insulators that were installed at different locations. The measurement of arithmetical mean surface roughness is done, and statistical analysis is implemented in this study. Three groups of insulators labeled as 6 years, 12 years, 18 years, and with their respective controlled samples are tested using a surface roughness tester. Data measurements from the testing are analyzed in conjunction with visual observation to investigate an indication of surface degradation within the groups. Further statistical analysis is applied for the comparison of the surface roughness conditions. In order to observe the environmental stress factors that will affect the roughness condition, within the installation area, the virtual three-dimensional mapping program represented the Earth based on satellite imagery is utilized. The correlation analysis on all that three groups has indicated the positive outcomes with the roughness increased with respect to the age of insulator that located in quite similar environmental stress conditions. Regardless of the age of an insulator, the degradation due to surface roughness condition can be used to indicate what levels of environmental stress around the installation area have.